A curcumin-loaded liquid crystal precursor mucoadhesive system for the treatment of vaginal candidiasis - Salmazi, Rafael [UNESP]; Calixto, Giovana [UNESP]; Bernegossi, Jéssica [UNESP]; Ramos, Matheus Aparecido dos Santos [UNESP]; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (International Journal Of Nanomedicine, 2015)
Women often develop vaginal infections that are caused primarily by organisms of the genus Candida. The current treatments of vaginal candidiasis usually involve azole-based antifungals, though fungal resistance to these compounds has become prevalent. Therefore, much attention has been given to molecules with antifungal properties from natural sources, such as curcumin (CUR). However, CUR has poor solubility in aqueous solvents and poor oral bioavailability. This study attempted to overcome this problem by developing, characterizing, and evaluating the in vitro antifungal action of a CUR-loaded liquid crystal precursor mucoadhesive system (LCPM) for vaginal administration. A low-viscosity LCPM (F) consisting of 40% wt/wt polyoxpropylene-(5)-polyoxyethylene-(20)-cetyl alcohol, 50% wt/wt oleic acid, and 10% wt/wt chitosan dispersion at 0.5% with the addition of 16% poloxamer 407 was developed to take advantage of the lyotropic phase behavior of this formulation. Notably, F could transform into liquid crystal systems when diluted with artificial vaginal mucus at ratios of 1:3 and 1:1 (wt/wt), resulting in the formation of F30 and F100, respectively. Polarized light microscopy and rheological studies revealed that F behaved like an isotropic formulation, whereas F30 and F100 behaved like an anisotropic liquid crystalline system (LCS). Moreover, F30 and F100 presented higher mucoadhesion to porcine vaginal mucosa than F. The analysis of the in vitro activity against Candida albicans revealed that CUR-loaded F was more potent against standard and clinical strains compared with a CUR solution. Therefore, the vaginal administration of CUR-loaded LCPMs represents a promising platform for the treatment of vaginal candidiasis.
Keywords: Candida albicans; Liquid crystalline systems; Mucoadhesive polymers; Nanostructured drug delivery systems; Vaginal administration